Sememe Heredity of Action Semantics: Evidence From the Priming Effect and Prospective Memory - Yu, Zhanyu; Ma, Yue; Wang, Lijuan (Frontiers in Psychology, 2020)
This study designed two experiments around sememe heredity of action semantics. Experiment 1 explored the contribution degree of verb and noun item specificity in enactment effect of action memory through priming effect from the encoding stage directly. The results showed that verb-semantic priming quantity was larger under motor encoding, which further explained verb-semantic association might play a greater role in sememe heredity of action semantics. Experiment 2 used the dual-task paradigm to explore the effect action-related semantics on prospective memory. The results showed that under motor encoding condition, the target-related action semantics had a significant higher prospective memory accuracy than the target-independent action semantics. The same result was found under verbal encoding condition. Thus, the sememe heredity of action semantics may depend on the related associations of gerund phrases or semantic content rather than semantic processing form of external motor encoding.